Modified luminescent material and preparation method thereof, luminescent fiber composition, luminescent fiber material and preparation method thereof
By using luminescent materials with the same metal elements, coupling agents and spinning additives with the same metal elements in UHMWPE fibers, the problem of insufficient stability of existing high-strength and high-modulus fiber luminescent materials is solved, and efficient fiber preparation and industrial application are achieved.
Patent Information
- Application Number
- CN202310875561.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-07-17
AI Technical Summary
The existing high-strength and high-modulus UHMWPE fiber luminescent materials have poor stability and have not been promoted in industrialization, and the combination force and stability of existing luminescent fiber materials have limited their application.
Using luminescent materials containing the same metal elements and coupling agents, through step-by-step preparation and ultrasonic dissolution technology, a uniform modified luminescent material is formed, and mixed with ultra-high molecular weight polyethylene spinning additives are prepared to produce excellent optical and mechanical Performance of luminous fibers.
It improves the stability and optical properties of optical fibers, extends service life, and reduces production costs, and is suitable for industrial promotion.
Smart Images

Figure CN119321002A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to a modified luminescent material and a preparation method thereof, a luminescent fiber composition, a luminescent fiber material and a preparation method thereof. Background Art
[0002] Ultra-high molecular weight polyethylene (UHMWPE) fiber, also known as high-strength high-modulus polyethylene fiber, is one of the three major high-tech fibers in the world today, along with carbon fiber and aramid. UHMWPE fiber is a fiber made by spinning and super-stretching polyethylene with a molecular weight of more than 1 million. It has mechanical properties such as high strength, high modulus, low density, impact resistance, wear resistance and low elongation at break. It is widely used in bulletproof protection, marine engineering, transportation, sports equipment, biomedicine and home textile products, and has a large demand in military and civilian dual-use fields.
[0003] With the development of science and technology, fiber raw materials with single properties can no longer meet people's growing demand for functional textiles. In the field of ultra-high molecular weight polyethylene fibers, although its application prospects are broad and many fiber materials based on UHMWPE have been developed, there are still deficiencies in high-strength and high-modulus UHMWPE fibers with luminous properties.
[0004] CN114808188A discloses a blue-green two-color self-luminous fiber and a preparation method thereof, which includes a skin layer and a core layer, wherein the skin layer includes nylon and rare earth magnesium strontium silicate long afterglow luminescent material, and the core layer includes polyester and rare earth strontium aluminate luminescent material. Currently, it has not been industrialized and promoted for application, and the fiber matrix is limited to nylon and polyester, and is not suitable for ethylene or polypropylene. In addition, the bonding force and stability between the core layer and the skin layer are also poor, which is not conducive to the preparation of high-strength and high-modulus luminescent fibers.
[0005] CN111962180A discloses a red long afterglow luminous composite fiber filament and a preparation method thereof, wherein the red long afterglow luminous composite fiber filament comprises a skin layer and a core layer, wherein the core layer comprises polyester and SrAl2O4:Eu 2+ ,Dy 3+ The luminescent material, whose cortex includes nylon 6 and a red fluorescent light color converter, has not yet been industrially promoted and applied. In addition, the rare earth aluminate luminescent material is easily affected by moisture in the air and has unstable properties, which limits its service life.
[0006] CN110318109A discloses a rare earth luminous fiber, which is intended to provide a rare earth luminous fiber that is resistant to high temperature and denaturation and has strong practicality. The invention is applicable to the field of textile material technology and has not yet been industrialized and promoted. Moreover, the cellulose fiber used has a high production cost, is easily affected by moisture, has poor toughness and corrosion resistance, and is therefore not conducive to the mechanical properties and dimensional stability of the product.
[0007] CN109913972A discloses a luminous composite fiber and a preparation method thereof. The preparation method adopted is simple, and the amount of silk fibroin and long afterglow rare earth can be selected according to different afterglow function requirements. Silk fibroin and long afterglow rare earth do not cause any damage to the structure and performance of the blended fiber itself, and it has not yet been industrialized and promoted. In addition, silk fibroin has low strength and modulus, is easily hydrolyzed, and has poor tolerance to chemicals such as acids and alkalis, which limits its application field.
[0008] Therefore, it is necessary to develop a UHMWPE fiber with good stability and luminescence properties. Summary of the invention
[0009] The purpose of the present invention is to overcome the problems of poor stability and insufficient industrialization of luminescent materials in the prior art, and to provide a modified luminescent material and a preparation method thereof, a luminescent fiber composition, a luminescent fiber material and a preparation method thereof.
[0010] In order to achieve the above object, the first aspect of the present invention provides a modified luminescent material, wherein the material comprises: 10-450 parts by weight of luminescent material and 5-50 parts by weight of coupling agent; wherein the luminescent material and the coupling agent contain the same metal element.
[0011] The second aspect of the present invention provides a method for preparing a modified luminescent material, wherein, at a first temperature, the luminescent material is dissolved in a first solvent to obtain a first solution, and at a second temperature, the coupling agent is dissolved in a second solvent to obtain a second solution; the first solution and the second solution are mixed and dried to obtain the modified luminescent material; wherein the luminescent material is 10-450 parts by weight and the coupling agent is 5-50 parts by weight, and the luminescent material and the coupling agent contain the same metal element.
[0012] The third aspect of the present invention provides a composition for preparing luminescent fibers, wherein the composition comprises: ultra-high molecular weight polyethylene, a modified luminescent material, a spinning aid and a solvent; wherein the modified luminescent material is the aforementioned modified luminescent material or a modified luminescent material prepared by the aforementioned method.
[0013] The fourth aspect of the present invention provides a luminescent fiber material, wherein the luminescent fiber has a fineness of 2-200 dtex, a breaking strength of 10-50 cN / dtex, an initial modulus of 500-1700 cN / dtex, a breaking elongation of 1-5%, an elongation variation coefficient of 1-7 CV%, a strength variation coefficient of 1-5 CV%, and an initial brightness of 0.5-6 cd / m 2 , the afterglow time is 0.5-6h; the luminous fiber is made by spinning the above-mentioned composition.
[0014] The fifth aspect of the present invention provides a method for preparing a luminescent fiber material, wherein ultra-high molecular weight polyethylene, a modified luminescent material and a spinning aid are uniformly mixed in a solvent and swelled, the uniformly mixed swelling liquid is extruded to obtain gel filaments, and the gel filaments are quenched, dried, stretched and wound to obtain luminescent fibers.
[0015] Through the above technical solution, the excellent effects achieved by the present invention are as follows:
[0016] (1) The coupling agent and the luminescent material contain the same metal element, which gives the two similar structures and functional groups, and good compatibility with each other, so that the coupling agent and the luminescent material can be mixed more fully, and the stability of the modified luminescent material is improved, and it is not easy to hydrolyze; further, the optical properties, mechanical properties and stability of the prepared luminescent fiber material are improved;
[0017] (2) In the preparation process of the luminescent fiber material, the modified luminescent material is evenly dispersed in the ultra-high molecular weight polyethylene through the step-by-step preparation process, and the solvent of each module can be recycled, which is conducive to industrial promotion;
[0018] (3) The components in the composition of the luminescent fiber work synergistically, so that the filler is dispersed more evenly in the ultra-high molecular weight polyethylene, the agglomeration behavior of the components of the composition in the ultra-high molecular weight polyethylene is reduced, and the stability of the luminescent fiber is improved; and the modified luminescent material with a specific proportion and composition is added thereto, so that the luminescent fiber maintains good mechanical properties while improving the photon utilization efficiency and luminescence quantum yield, so that it has a higher initial brightness and a longer afterglow time, giving the luminescent fiber material excellent optical properties, mechanical properties and stability, and enabling the luminescent fiber to be used within a certain humidity range, not easily hydrolyzed and having a longer service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a microscope image of the luminescent fiber obtained in Example 4 of the present invention;
[0020] Figure 2 is a schematic structural diagram of the luminescent fiber of the present invention;
[0021] Figure 3 It is a schematic diagram of the process of the fiber spinning equipment of the present invention;
[0022] Figure 4 It is a schematic diagram of the fiber spinning process of the present invention. DETAILED DESCRIPTION
[0023] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0024] The first aspect of the present invention provides a modified luminescent material, wherein the material comprises 10-450 parts by weight of a luminescent material and 5-50 parts by weight of a coupling agent; wherein the luminescent material and the coupling agent contain the same metal element.
[0025] The inventor unexpectedly discovered in the experiment that when the luminescent material and the coupling agent contain the same metal element, the functional groups and structures of the luminescent material and the coupling agent are common, they have good compatibility with each other, are not easily hydrolyzed, and are more likely to form a uniform and stable material. At the same time, the photon utilization efficiency and luminescence quantum yield are improved, so that the modified luminescent material has excellent luminescence performance.
[0026] Furthermore, the material comprises: 30-240 parts by weight of a luminescent material and 10-30 parts by weight of a coupling agent; wherein the metal element is Ti.
[0027] According to the present invention, the mass ratio of the luminescent material to the coupling agent is 2-9:1, preferably 3-8:1.
[0028] In the present invention, when the weight ratio of the luminescent material to the coupling agent is 3.5:1, the luminescent performance of the modified luminescent material is the best. When the content of the coupling agent is too high, the reduction of its quenching effect is insufficient to compensate for the reduction of the excitation light quantum efficiency, resulting in a decrease in optical performance.
[0029] According to the present invention, the luminescent material is selected from titanates, preferably Ca2Zn4Ti5O 36 :Pr 3+ Mg 0.2 Ca 0.8 TiO3:Pr 3+ and CaTiO3:Pr 3+ At least one of .
[0030] According to the present invention, the coupling agent is selected from titanate coupling agents.
[0031] In the present invention, the specific coupling agent has the advantage of being applicable to a wide range of fillers, coupling agents and resins compared to coupling agents on the market. Specifically, the titanate coupling agent is applicable to fillers, coupling agents and resins, and has a wide range of applications, while the widely used silane coupling agents on the market are mainly applicable to thermosetting resins. Silane coupling agents are only effective for fillers containing silicon elements, while titanate coupling agents are applicable to a variety of fillers and have a wide range of applicable resins; at the same time, they can play a synergistic role with titanates to enhance the mechanical properties of fibers and help improve luminescence properties.
[0032] Furthermore, the luminescent material is Ca2Zn4Ti5O 36 :Pr 3+ .
[0033] Furthermore, the coupling agent is selected from at least one of a monoalkoxy titanate coupling agent, a chelate titanate coupling agent and a coordination titanate coupling agent, more preferably a monoalkoxy pyrophosphate titanate coupling agent and / or a monoalkoxy fatty acid ester titanate coupling agent, most preferably a monoalkoxy pyrophosphate titanate coupling agent.
[0034] The second aspect of the present invention provides a method for preparing a modified luminescent material, wherein, at a first temperature, the luminescent material is dissolved in a first solvent to obtain a first solution, and at a second temperature, the coupling agent is dissolved in a second solvent to obtain a second solution; the first solution and the second solution are mixed and dried to obtain the modified luminescent material; wherein the luminescent material is 10-450 parts by weight and the coupling agent is 5-50 parts by weight, and the luminescent material and the coupling agent contain the same metal element.
[0035] According to the present invention, the luminescent material is 30-240 parts by weight and the coupling agent is 10-30 parts by weight; and the metal element is Ti.
[0036] According to the present invention, the mass ratio of the luminescent material to the coupling agent is 2-9:1, preferably 3-8:1.
[0037] According to the present invention, the luminescent material is dissolved in a first solvent and ultrasonically treated for 0.5-6 hours, and the coupling agent is dissolved in a second solvent and ultrasonically treated for 1-5 hours.
[0038] In the present invention, the luminescent material and the coupling agent are dissolved in the first solvent and the second solvent respectively at different temperatures, and ultrasound is used to make the dissolution more complete, thereby bringing about deep infiltration and mixing at the molecular level, and does not rely on high-temperature stirring, effectively avoiding the damage to the structural stability of the substrate caused by high temperature.
[0039] In the present invention, ultrasound can achieve accelerated dissolution, sufficient mixing and efficient reaction at the molecular level between the compound and the solvent under mild conditions (such as room temperature, without mechanical stirring), thereby improving the reaction efficiency and blending effect, and helping to achieve energy conservation, environmental protection, cost reduction and efficiency improvement in the process.
[0040] According to the present invention, the luminescent material is dissolved in a first solvent and subjected to ultrasound for 2-4 hours, and the coupling agent is dissolved in a second solvent and subjected to ultrasound for 2-3 hours.
[0041] According to the present invention, the first temperature is 10-120°C.
[0042] According to the present invention, the second temperature is 10-35°C.
[0043] In the present invention, the first temperature and the second temperature satisfying the above range can enhance the compatibility between the luminescent material and the coupling agent, so that the finally prepared modified luminescent material has improved stability and good luminescent performance.
[0044] Furthermore, the first temperature is 20-100°C.
[0045] Furthermore, the second temperature is 20-30°C.
[0046] According to the present invention, the weight ratio of the luminescent material to the first solvent is 0.05-0.2:1.
[0047] According to the present invention, the weight ratio of the coupling agent to the second solvent is 0.01-0.25:1.
[0048] In the present invention, when reactants satisfying the weight ratio in the above range react, they have good compatibility with each other and are not easily hydrolyzed. The modified luminescent material finally prepared is uniform and stable and has excellent luminescent properties.
[0049] Furthermore, the weight ratio of the luminescent material to the first solvent is 0.1-0.15:1.
[0050] Furthermore, the weight ratio of the coupling agent to the second solvent is 0.05-0.15:1.
[0051] According to the present invention, the first solvent and the second solvent are each independently selected from at least one of decahydronaphthalene, chloroform, and tetrahydrofuran, preferably decahydronaphthalene and / or chloroform.
[0052] In the present invention, the first solvent and the second solvent in the preparation method of the modified luminescent material are both low-boiling point solvents and can be recycled. The recycled solvents can be reused or reused in the dry spinning module, which reduces costs and is environmentally friendly.
[0053] In the present invention, the luminescent material and coupling agent described in the second aspect are respectively as described above and will not be described in detail.
[0054] The third aspect of the present invention provides a composition for preparing luminescent fibers, wherein the composition comprises: ultra-high molecular weight polyethylene, a modified luminescent material, a spinning aid and a solvent; wherein the modified luminescent material is the aforementioned modified luminescent material or a modified luminescent material prepared by the aforementioned method.
[0055] According to the present invention, based on the amount of the solvent, the amount of the ultra-high molecular weight polyethylene is 5wt%-20wt%, preferably 7wt%-15wt%.
[0056] According to the present invention, based on the amount of the ultra-high molecular weight polyethylene, the amount of the modified luminescent material is 2wt%-20wt%, and the amount of the spinning aid is 0.1wt%-1.5wt%.
[0057] In the present invention, the specific amount of each component in the composition can make the fiber prepared by spinning the composition have good mechanical properties and optical properties at the same time; when the modified luminescent material is lower than this content, the physical crosslinking points are insufficient and the mechanical properties of the fiber are poor; when the modified luminescent material is higher than this content, the optical properties are saturated and will not increase any further, but as the content increases, it will affect the crystallinity and integrity of the fiber chain segments, and the mechanical properties will decrease.
[0058] Preferably, based on the amount of the ultra-high molecular weight polyethylene, the amount of the modified luminescent material is 2wt%-10wt%, and the amount of the spinning aid is 0.6wt%-1.5wt%.
[0059] Furthermore, the inventors of the present invention found that when the content of the modified luminescent material is 9wt%, the luminescent fiber has both the best mechanical properties and optical properties.
[0060] According to the present invention, the viscosity average molecular weight of the ultra-high molecular weight polyethylene is 1 million to 20 million g / mol, preferably 2 million to 6 million g / mol.
[0061] According to the present invention, the spinning aid comprises an antistatic agent, an antioxidant and a lubricant.
[0062] In the present invention, the spinning aid of specific components can improve the molding processability and processing stability of the fiber, solve the surface migration problem of the material, reduce the melt viscosity, shorten the plasticizing time, increase the unit output, and enhance the stability, creep resistance, oxidation resistance and aging resistance of the luminescent fiber product.
[0063] According to the present invention, the antistatic agent is selected from at least one of sulfates, phosphates and polyethylene glycol derivatives, preferably at least one of alkyl phosphates, alkyl sulfonates and polyoxyethylene alkyl phosphate salts.
[0064] According to the present invention, the antioxidant is selected from at least one of antioxidant 1076, antioxidant 1010, antioxidant 168, antioxidant 1178 and 2,6-di-tert-butyl-p-cresol, preferably antioxidant 168 and / or 2,6-di-tert-butyl-p-cresol.
[0065] According to the present invention, the lubricant is selected from at least one of stearic acid, butyl stearate, oleamide, ethylene bisstearamide, polyethylene wax and low molecular weight polypropylene, preferably stearic acid and / or butyl stearate.
[0066] According to the present invention, based on the amount of ultra-high molecular weight polyethylene, the content of the antistatic agent is 0.02wt%-0.4wt%, the content of the antioxidant is 0.04wt%-0.6wt%, and the content of the lubricant is 0.02wt%-0.5wt%.
[0067] In the present invention, the specific content of spinning aid has a modifying effect and good compatibility and internal plasticization of the fiber resin matrix, which solves the surface migration problem of the plasticizer, can improve the molding processability and processing stability of the fiber, reduce the melt viscosity, shorten the plasticizing time, increase the unit output, and enhance the stability, creep resistance, oxidation resistance and aging resistance of the luminous fiber product.
[0068] Furthermore, based on the amount of ultra-high molecular weight polyethylene, the content of the antistatic agent is 0.05wt%-0.2wt%, the content of the antioxidant is 0.1wt%-0.3wt%, and the content of the lubricant is 0.08wt%-0.3wt%.
[0069] According to the present invention, the solvent is selected from at least one of benzene, 1,2,3,4-tetralin, decahydronaphthalene and xylene, preferably decahydronaphthalene and / or 1,2,3,4-tetralin.
[0070] The fourth aspect of the present invention provides a luminescent fiber material, wherein the luminescent fiber has a fineness of 2-200 dtex, a breaking strength of 10-50 cN / dtex, an initial modulus of 500-1700 cN / dtex, a breaking elongation of 1-5%, an elongation variation coefficient of 1-7 CV%, a strength variation coefficient of 1-5 CV%, and an initial brightness of 0.5-6 cd / m 2 , the afterglow time is 0.5-6h; the luminous fiber is made by spinning the above-mentioned composition.
[0071] In the present invention, the stability of the fiber is characterized by the coefficient of variation of elongation and the coefficient of variation of strength. The luminescent fiber material of the present invention has strong initial brightness, long afterglow time, good mechanical properties and high stability.
[0072] Figure 2 It is a structural schematic diagram of the luminescent fiber of the present invention. The modified luminescent material is uniformly distributed in the ultra-high molecular weight polyethylene matrix, which can reduce the variation rate of mechanical properties and achieve uniform distribution of the luminescent area, bringing about a significant improvement in the mechanical and optical properties of the fiber product and an improvement in the uniformity of product quality, thereby meeting the needs of actual application fields.
[0073] The fifth aspect of the present invention provides a method for preparing a luminescent fiber material, wherein ultra-high molecular weight polyethylene, a modified luminescent material and a spinning aid are uniformly mixed in a solvent and swelled, the uniformly mixed swelling liquid is extruded to obtain gel filaments, and the gel filaments are quenched, dried, stretched and wound to obtain luminescent fibers.
[0074] According to the present invention, the quenching solvent is at least one of toluene, 1,2,3,4-tetralin, decalin, xylene, water and ethanol; preferably water and / or ethanol.
[0075] The spinning method in the present invention is a common dry spinning method in the art, and the specific equipment is as follows: Figure 3 As shown, the process flow of the present invention is as short as Figure 4 As shown, the solvent of dry spinning overlaps with the solvent used to prepare the modified luminescent material in the front-end step, so the solvent can be recycled, continuous production can be achieved, production costs are reduced, and it is beneficial to environmental protection.
[0076] According to the present invention, the swelling temperature is 70-120° C., preferably 90-110° C.; the swelling time is 1-8 h, preferably 2-5 h.
[0077] According to the present invention, the extrusion rate is 0-40 m / min, preferably 15-30 m / min.
[0078] According to the present invention, the quenching temperature is -50°C to 20°C, preferably -15°C to -5°C; the quenching time is 0.2-5 min, preferably 0.5-2 min.
[0079] According to the present invention, the drying is carried out in a drying hot box, and the drying method is blowing, and the wind direction is opposite to the traveling direction of the gel filaments.
[0080] According to the present invention, the blowing gases are each independently selected from at least one of air, nitrogen, carbon dioxide and an inert gas; preferably at least one of air, nitrogen, carbon dioxide, argon and helium.
[0081] According to the invention, pre-drawing is carried out in a drawing hot box.
[0082] According to the present invention, the pre-stretching multiple is 1-10 times, preferably 1-5 times; the pre-stretching temperature is 100-150°C, preferably 110-130°C.
[0083] According to the present invention, the multi-stage drafting includes primary drafting, secondary drafting and tertiary drafting, the multiple of the primary drafting is 4-6 times, preferably 4.5-5.5 times; the temperature of the primary drafting is 100-140°C, preferably 125-140°C.
[0084] According to the present invention, the multiple of the secondary drawing is 1-3 times, preferably 1.5-2.5 times; the temperature of the secondary drawing is 130-150°C, preferably 135-145°C.
[0085] According to the present invention, the multiple of the three-stage drawing is 1-2 times, preferably 1.2-1.5 times; the temperature of the three-stage drawing is 140-160°C, preferably 145-155°C.
[0086] The present invention will be described in detail below through examples.
[0087] Testing method for breaking strength: Use Instron 1122 universal material testing machine: Stretch the prepared fibers under different conditions, and control the environment according to the requirements of the test method standard for reinforced materials. The temperature is 23±2℃ and the relative humidity is (50±10)%. The stretching speed is 250mm / min; the clamp is the rope test clamp produced by INSTRON, which can ensure that the sample does not slip during the test; the clamping distance is 500mm. Stretch until the fiber breaks, and the instrument automatically obtains the result. Each reel of silk is tested 10 times on average, and the average value is taken. The software gives the breaking strength result;
[0088] The testing method of elongation at break is the same as above, and the result is given by the software;
[0089] The initial modulus is tested in the same way as above, and the result is given by the software;
[0090] The test method of elongation variation coefficient is the same as above, and the result is given by the software;
[0091] The test method of the strong coefficient of variation is the same as above, and the results are given by the software;
[0092] The microscope selected was the Caikang Optics CKC2000 high-definition digital imaging microscope.
[0093] The initial brightness test method is: use the PR-305 long afterglow fluorescence tester. When testing, select a standard light source with an excitation light intensity of 1000lx for continuous excitation for 10 minutes. After the excitation is completed, record the initial brightness of the afterglow;
[0094] The afterglow time detection method is: use PR-305 long afterglow fluorescence tester. When testing, select a standard light source with an excitation light intensity of 1000lx for continuous excitation for 10 minutes. After the excitation is completed, record the afterglow brightness decay to 0.00032cd / m 2 The time required is the afterglow time of the material.
[0095] Luminescent material: Ca2Zn4Ti5O 36 :Pr 3+ Mg0.2 Ca 0.8 TiO3:Pr 3+ 、CaTiO3:Pr 3+ 、SrAl2O4:Eu 2+ 、Dy 3+ Sr3MgSi2O8:Eu 2+ 、Dy 3+ ZnWO4:Eu 3+ and Zn3(PO4):Mn 2+ , purchased from Aladdin Reagent Company;
[0096] KH550, monoalkoxy pyrophosphate type titanate coupling agent, monoalkoxy fatty acid ester type titanate coupling agent, chelate type titanate coupling agent, coordination type titanate coupling agent, etc. were purchased from Anaiji Reagent Company;
[0097] Ultra-high molecular weight polyethylene A1 (viscosity average molecular weight of 4 million g / mol) was purchased from Lianle Chemical;
[0098] Ultra-high molecular weight polyethylene A2 (viscosity average molecular weight 500,000 g / mol) was purchased from Yanshan Petrochemical;
[0099] Antistatic agents such as alkyl sulfate, phosphate, polyethylene glycol derivatives, alkyl phosphate, alkyl sulfonate, polyoxyethylene alkyl phosphate, polyoxyethylene alkyl phosphate salt were purchased from Bede Reagent Company;
[0100] Antioxidant 1076, antioxidant 1010, antioxidant 168, antioxidant 1178, and 2,6-di-tert-butyl-p-cresol were purchased from Aladdin Reagent Company;
[0101] Lubricants such as stearic acid, butyl stearate, oleamide, ethylene bis stearamide, polyethylene wax, and low molecular weight polypropylene were purchased from Myrel Reagent Company;
[0102] Decalin, chloroform, and methanol were purchased from Sinopharm Reagent Chemical Company.
[0103] Preparation Example 1
[0104] At 25 °C, 40 g of Ca2Zn4Ti5O 36 :Pr 3+ Add to 400g of decahydronaphthalene, and ultrasonicate for 2h to obtain a first solution; at 25°C, add 10g of monoalkoxy pyrophosphate type titanate coupling agent to 180g of decahydronaphthalene, and ultrasonicate for 3h to obtain a second solution; mix the first solution and the second solution and dry them to obtain modified luminescent material preparation example 1.
[0105] Preparation Examples 2-12 and Comparative Preparation Examples 1-6 were carried out according to the method of Preparation Example 1, and the specific addition conditions are shown in Table 1.
[0106] Table 1
[0107]
[0108] Table 1 (continued)
[0109]
[0110]
[0111] Table 1 (continued)
[0112]
[0113] Table 1 (continued)
[0114]
[0115] Table 1 (continued)
[0116]
[0117]
[0118] Table 1 (continued)
[0119]
[0120] Example 1
[0121] 5000g of ultra-high molecular weight polyethylene A1 was added to 45000g of decalin, and then 450g of Preparation Example 1, 7.5g of antistatic agent, 10g of antioxidant and 12.5g of lubricant were added and mixed evenly for swelling. The swelling temperature was 100°C, the swelling time was 4h, and the extrusion rate was 2m / min; the quenching temperature was -10°C, and the quenching time was 1min; the drying hot box temperature was 60°C; the pre-stretching multiple was 2 times, and the temperature of the stretching hot box was 110°C; the primary stretching multiple was 5 times, and the primary stretching temperature was 138°C; the secondary stretching multiple was 1.5 times, and the secondary stretching temperature was 144°C; the tertiary stretching multiple was 1.2, and the tertiary stretching temperature was 148°C.
[0122] Examples 2-12, 14-25 and Comparative Examples 1-7 were implemented according to the method of Example 1, and the addition of specific components is shown in Table 2.
[0123] Table 2 Table 2 (continued)
[0124]
[0125]
[0126] Table 2 (continued)
[0127]
[0128] Table 2 (continued)
[0129]
[0130]
[0131] Table 2 (continued)
[0132]
[0133] Table 2 (continued)
[0134]
[0135] Table 2 (continued)
[0136] Table 2 (continued)
[0137]
[0138] Example 13
[0139] 5000g of ultra-high molecular weight polyethylene A1 was added to 45000g of decahydronaphthalene, and then 450g of Preparation Example 2, 7.5g of antistatic agent, 10g of antioxidant and 12.5g of lubricant were added and mixed evenly for swelling. The swelling temperature was 100°C, the swelling time was 4h, and the extrusion rate was 3m / min; the quenching temperature was 0°C, and the quenching time was 1min; the drying hot box temperature was 60°C; the pre-stretching multiple was 2 times, and the temperature of the stretching hot box was 110°C; the primary stretching multiple was 4.6 times, and the primary stretching temperature was 136°C; the secondary stretching multiple was 1.5 times, and the secondary stretching temperature was 145°C; the tertiary stretching multiple was 1.2, and the tertiary stretching temperature was 150°C.
[0140] The mechanical parameters of the fibers prepared in Examples 1-25 and Comparative Examples 1-7 are shown in Table 3.
[0141] Table 3
[0142]
[0143]
[0144] The optical parameters of the fibers prepared in Examples 1-25 and Comparative Examples 1-7 are shown in Table 4.
[0145] Table 4
[0146]
[0147]
[0148] It can be seen from the results in Table 3 and Table 4 that, compared with Examples 1-12, the type of luminescent material will affect the performance of the luminescent fiber. When the luminescent material and the coupling agent in the modified luminescent material contain the same element, the luminescent fiber finally prepared can have both mechanical and optical properties and stronger stability. Among them, the luminescent material is Ca2Zn4Ti5O 36 :Pr 3 + Mg 0.2 Ca 0.8 TiO3:Pr 3+ and CaTiO3:Pr 3+ The effect is good when the luminescent material is Ca2Zn4Ti5O 36 :Pr 3+ When the performance is better;
[0149] Further, in Examples 2-7, the dosage of the luminescent material and the coupling agent is adjusted. The functional groups and structures of the luminescent material and the coupling agent are common, the compatibility between them is good, and they are not easily hydrolyzed, and it is easier to form a uniform and stable material, while improving the photon utilization efficiency and the luminescence quantum yield. When the content of the coupling agent is too high, the reduction in its quenching effect is insufficient to compensate for the reduction in the excitation light quantum efficiency, resulting in a decrease in optical performance. Therefore, the specific dosage of the luminescent material and the coupling agent makes the photon utilization efficiency and the luminescence quantum yield of the modified luminescent material higher, and has excellent luminescence performance.
[0150] Microscope image of the luminescent fiber obtained in Example 4 (see Figure 1 ) It can be seen that the prepared long afterglow luminescent ultra-high molecular weight polyethylene fibers have similar diameters, size uniformity and smooth surfaces. Products (a) and (b) from different batches under the same conditions have similar morphologies and structures, which can achieve the repeatability of fiber spinning preparation. The prepared fibers have good surface morphology indicators, dimensional stability and spinnability.
[0151] In Example 14 to Example 21, the amount of the modified luminescent material and the ultra-high molecular weight polyethylene was adjusted. Based on the amount of the ultra-high molecular weight polyethylene, the modified luminescent material is preferably 2wt%-20wt%, and more preferably 2wt%-10wt%. If the content of the modified luminescent material is too little, the luminescent intensity will be affected. If the content is too high, it will not be conducive to improving the luminescent quantum yield and the crystallinity of the fiber, which will affect the luminescent properties and mechanical properties.
[0152] In Example 22 and Example 23, the spinning aid is adjusted. Based on the total mass of the spinning aid, preferably, the content of the antistatic agent is 0.05wt%-0.2wt%, preferably alkyl phosphate, the content of the antioxidant is 0.1wt%-0.3wt%, preferably antioxidant 168, and the content of the lubricant is 0.08wt%-0.3wt%, preferably polyethylene wax; the spinning aid of specific components can improve the molding processability and processing stability of the fiber, solve the surface migration problem of the material, and can reduce the melt viscosity, shorten the plasticizing time, and increase the unit output at the same time. The obtained luminescent fiber material has excellent stability, creep resistance, oxidation resistance and aging resistance;
[0153] In Example 24 and Example 25, the concentration and molecular weight of ultra-high molecular weight polyethylene were adjusted. When the polymer concentration was 7wt%-15wt% and the molecular weight was 4 million g / mol, it was more conducive to the preparation of luminescent fiber materials. Too high a polymer concentration will lead to too high a viscosity during the preparation process, making processing and drafting difficult and affecting the final performance of the product; when the molecular weight of the polymer is too low, it will have a negative impact on the mechanical properties of the final luminescent fiber material; too high a molecular weight will lead to processing difficulties, affect post-spinning drafting, and further affect the mechanical properties;
[0154] Comparative Examples 1-7 adjusted the luminescent system and coupling agent outside the preferred range, proving that the coupling agent and the luminescent material in the examples have the same metal element, and the similarity of their structures and functional groups have excellent compatibility, so that the coupling agent and the luminescent material are mixed more fully, thereby improving the stability and hydrolysis stability of the modified luminescent material. The luminescent fiber prepared from the modified luminescent material has excellent mechanical and optical properties, and the stability is also greatly enhanced.
[0155] At the same time, the low-boiling point solvent in the specific implementation can be recycled and reused in each module, which reduces the cost and is conducive to industrial promotion.
[0156] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A modified luminescent material, characterized in that: The material comprises: 10-450 parts by weight of luminescent material and 5-50 parts by weight of coupling agent; Wherein, the luminescent material and the coupling agent contain the same metal element.
2. The modified luminescent material according to claim 1, wherein: The material comprises: 30-240 parts by weight of the luminescent material and 10-30 parts by weight of the coupling agent; Wherein, the metal element is Ti; Preferably, the mass ratio of the luminescent material to the coupling agent is 2-9:1, preferably 3-8:
1.
3. The modified luminescent material according to claim 1 or 2, wherein: The luminescent material is selected from titanates, preferably Ca2Zn4Ti5O 36 :Pr 3+ Mg 0.2 Ca 0.8 TiO3:Pr 3+ and CaTiO3:Pr 3+ At least one of the following, more preferably Ca2Zn4Ti5O 36 :Pr 3+ ; Preferably, the coupling agent is selected from titanate coupling agents, preferably at least one of monoalkoxy titanate coupling agents, chelate titanate coupling agents and coordination titanate coupling agents, more preferably monoalkoxy pyrophosphate titanate coupling agents and / or monoalkoxy fatty acid ester titanate coupling agents, most preferably monoalkoxy pyrophosphate titanate coupling agents.
4. A method for preparing a modified luminescent material, characterized in that: At a first temperature, a luminescent material is dissolved in a first solvent to obtain a first solution, and at a second temperature, a coupling agent is dissolved in a second solvent to obtain a second solution; the first solution and the second solution are mixed and dried to obtain the modified luminescent material; wherein the luminescent material is 10-450 parts by weight and the coupling agent is 5-50 parts by weight, and the luminescent material and the coupling agent contain the same metal element.
5. The preparation method according to claim 4, wherein The luminescent material is 30-240 parts by weight and the coupling agent is 10-30 parts by weight; the metal element is Ti; Preferably, the mass ratio of the luminescent material to the coupling agent is 2-9:1, preferably 3-8:1; Preferably, the luminescent material is dissolved in the first solvent and ultrasonically treated for 0.5-6 hours, preferably 2-4 hours; the coupling agent is dissolved in the second solvent and ultrasonically treated for 1-5 hours, preferably 2-3 hours; Preferably, the first temperature is 10-120°C, preferably 20-100°C; Preferably, the second temperature is 10-35°C, preferably 20-30°C; Preferably, the weight ratio of the luminescent material to the first solvent is 0.05-0.2:1, preferably 0.1-0.15:1; Preferably, the weight ratio of the coupling agent to the second solvent is 0.01-0.25:1, preferably 0.05-0.15:1; Preferably, the first solvent and the second solvent are each independently selected from at least one of decahydronaphthalene, chloroform, and tetrahydrofuran, preferably decahydronaphthalene and / or chloroform.
6. A composition for preparing a luminescent fiber, characterized in that: The composition comprises: ultra-high molecular weight polyethylene, modified luminescent material, spinning aid and solvent; Wherein, the modified luminescent material is the modified luminescent material described in any one of claims 1 to 3, or the modified luminescent material prepared by the preparation method described in claim 4 or 5.
7. The composition according to claim 6, wherein Based on the amount of the solvent, the amount of the ultra-high molecular weight polyethylene is 5wt%-20wt%, preferably 7wt%-15wt%; Preferably, based on the amount of the ultra-high molecular weight polyethylene, the amount of the modified luminescent material is 2wt%-20wt%, and the amount of the spinning aid is 0.1wt%-1.5wt%; Preferably, based on the amount of the ultra-high molecular weight polyethylene, the amount of the modified luminescent material is 2wt%-10wt%, and the amount of the spinning aid is 0.6wt%-1.5wt%.
8. The composition according to claim 6 or 7, wherein The viscosity average molecular weight of the ultra-high molecular weight polyethylene is 1 million to 20 million g / mol, preferably 2 million to 6 million g / mol; Preferably, the spinning aid comprises an antistatic agent, an antioxidant and a lubricant; Preferably, the antistatic agent is selected from at least one of sulfates, phosphates and polyethylene glycol derivatives, preferably at least one of alkyl phosphates, alkyl sulfonates and polyoxyethylene alkyl phosphate salts; Preferably, the antioxidant is selected from at least one of antioxidant 1076, antioxidant 1010, antioxidant 168, antioxidant 1178 and 2,6-di-tert-butyl-p-cresol, preferably antioxidant 168 and / or 2,6-di-tert-butyl-p-cresol; Preferably, the lubricant is selected from at least one of stearic acid, butyl stearate, oleamide, ethylene bisstearamide, polyethylene wax and low molecular weight polypropylene, preferably stearic acid and / or butyl stearate; Preferably, based on the amount of ultra-high molecular weight polyethylene, the content of the antistatic agent is 0.02wt%-0.4wt%, the content of the antioxidant is 0.04wt%-0.6wt%, and the content of the lubricant is 0.02wt%-0.5wt%; Preferably, based on the amount of ultra-high molecular weight polyethylene, the content of the antistatic agent is 0.05wt%-0.2wt%, the content of the antioxidant is 0.1wt%-0.3wt%, and the content of the lubricant is 0.08wt%-0.3wt%; Preferably, the solvent is selected from at least one of benzene, 1,2,3,4-tetralin, decahydronaphthalene and xylene, preferably decahydronaphthalene and / or 1,2,3,4-tetralin.
9. A luminescent fiber material, characterized in that: The luminescent fiber has a fineness of 2-200 dtex, a breaking strength of 10-50 cN / dtex, an initial modulus of 500-1700 cN / dtex, a breaking elongation of 1-5%, an elongation variation coefficient of 1-7 CV%, a strength variation coefficient of 1-5 CV%, and an initial brightness of 0.5-6 cd / m 2 , afterglow time is 0.5-6h; The luminescent fiber is obtained by spinning the composition according to any one of claims 6 to 8.
10. A method for preparing a luminescent fiber material, characterized in that: In a solvent, ultra-high molecular weight polyethylene, modified luminescent material and spinning aid are uniformly mixed and swelled, and the uniformly mixed swelling liquid is extruded to obtain gel filaments. The gel filaments are quenched, dried, stretched and rolled to obtain luminescent fibers.
11. The preparation method according to claim 10, wherein: The quenching solvent is at least one of toluene, 1,2,3,4-tetralin, decalin, xylene, water and ethanol; preferably water and / or ethanol.
Citation Information
Patent Citations
Light-emitting compound fiber, preparing method thereof and light-emitting working clothes
CN109913972A
Rare earth noctilucent fiber and application thereof
CN110318109A
Red long-afterglow luminous composite fiber filament and preparation method thereof
CN111962180A
Polymer-rare earth up-conversion phosphor composite dielectric material for holographic display and preparation method thereof
CN101864312A
Functionalized rare-earth complex organic / inorganic hybrid luminescent material and preparation method thereof
CN104194776A